(untitled) - McCarthy, Alan (California, 2015)
Advanced Negotiation Techniques provides a wealth of material in a winning combination of practical experience and good research to give you a series of tools, techniques, and real-life examples to help you achieve your negotiation objectives. For 25 years and across 40 countries, the Resource Development Centre (RDC), run by negotiation experts Alan McCarthy and Steve Hay, has helped thousands of people to conduct successful negotiations of every type. Many RDC clients have been business professionals who have learned how to sell more successfully. Others have improved their buying skills. A few clients have applied the RDC techniques outside the business environment altogetherℓ́ℓfor instance, in such areas as international diplomatic services, including hostage and kidnap situations. As youℓ́ℓll discover, the RDC philosophy is centered on business ethics and a principled approach to negotiation that maximizes the value of the outcomes for both parties. It can even create additional value that neither party could find in isolation. In this book, you will learn: The ten golden rules for successful negotiations How to handle conflicts with your negotiating partners What hostage and kidnapping negotiations can teach managers negotiating in business settings How to ensure both sides perceive any agreement as a "win" Achieve higher-profit deals in difficult circumstances In the business world, negotiating with other companies, government officials, and even your colleagues is a fact of life. Advanced Negotiation Techniques takes you through a system for planning and conducting negotiations that will enable you and your team to achieve your negotiation objectives. This is an internationally tried and tested process, with many current Blue Chip organizations applying it daily for a simple reason: the techniques are easy to implement and they work. That makes this book essential reading for those who want to achieve their goals in any area of life.
Keywords: Negotiation in business,Đàm phán trong kinh doanh